Indoor Air Quality Prior to and Following School Building Renovation in a Mid-Atlantic School District - Sandra E. Zaeh (MDPI AG, 2021)
Children spend the majority of their time indoors, and a substantial portion of this time in the school environment. Air pollution has been shown to adversely impact lung development and has effects that extend beyond respiratory health. The goal of this study was to evaluate the indoor environment in public schools in the context of an ongoing urban renovation program to investigate the impact of school building renovation and replacement on indoor air quality. Indoor air quality (CO2, PM2.5, CO, and temperature) was assessed for two weeks during fall, winter, and spring seasons in 29 urban public schools between December 2015 and March 2020. Seven schools had pre- and post-renovation data available. Linear mixed models were used to examine changes in air quality outcomes by renovation status in the seven schools with pre- and post-renovation data. Prior to renovation, indoor CO measurements were within World Health Organization (WHO) guidelines, and indoor PM2.5 measurements rarely exceeded them. Within the seven schools with pre- and post-renovation data, over 30% of indoor CO2 measurements and over 50% of indoor temperatures exceeded recommended guidelines from the American Society of Heating, Refrigerating, and Air Conditioning Engineers. Following renovation, 10% of indoor CO2 measurements and 28% of indoor temperatures fell outside of the recommended ranges. Linear mixed models showed significant improvement in CO2, indoor PM2.5, and CO following school renovation. Even among schools that generally met recommendations on key guidelines, school renovation improved the indoor air quality. Our findings suggest that school renovation may benefit communities of children, particularly those in low-income areas with aging school infrastructure, through improvements in the indoor environment.